2010
DOI: 10.1002/chem.200901994
|View full text |Cite
|
Sign up to set email alerts
|

Noncovalent Synthesis of Hierarchical Zinc Phosphates from a Single Zn4O12P4 Double‐Four‐Ring Building Block: Dimensionality Control through the Choice of Auxiliary Ligands

Abstract: In contrast to the well-known reaction of phosphonic acids RP(O)(OH)(2) with divalent transition-metal ions that yields layered metal phosphonates [RPO(3)M(H(2)O)](n), the 2,6-diisopropylphenyl ester of phosphoric acid, dippH(2), reacts with zinc acetate in methanol under ambient conditions to afford tetrameric zinc phosphate [(ArO)PO(3)Zn(MeOH)](4) (1). The coordinated methanol in 1 can be readily exchanged by stronger Lewis basic ligands at room temperature. This strategy opens up a new avenue for building d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(11 citation statements)
references
References 100 publications
0
5
0
Order By: Relevance
“…In conclusion, we have prepared and characterized as eries of novel and structurally diverse alkylzinc complexes incorporating organophosphinate ligandso ft he general formula [RZn(O 2 PR' 2 )],a long with oxo-zinc phosphinate clusters, that is, [Zn 4 (m 4 -O)(O 2 PR' 2 ) 6 ]a nd the alkoxy(oxo)zinc cluster [Zn 4 (m 4 -O)(m 2 -OtBu)(dppha) 5 ]. Whereas inorganic-organic zinc clusters have been exploited as secondary building units of noncovalent porousm aterials, [17] our studies revealed that discrete [RZn(O 2 PR' 2 )]-type clusters act as shape-selective molecular buildingu nits and exhibit au nique capability for self-assembly, producing extended 3D networks with open channels. Moreover,a lkylzinc phosphinates appear to be efficient and easy-toprepareo rganozinc precursors of ZnO NCs capped with strongly anchored phosphinate ligand shells, which provides a new tool for the design, preparation,a nd functionalization of novel ZnO-based nanomaterials.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…In conclusion, we have prepared and characterized as eries of novel and structurally diverse alkylzinc complexes incorporating organophosphinate ligandso ft he general formula [RZn(O 2 PR' 2 )],a long with oxo-zinc phosphinate clusters, that is, [Zn 4 (m 4 -O)(O 2 PR' 2 ) 6 ]a nd the alkoxy(oxo)zinc cluster [Zn 4 (m 4 -O)(m 2 -OtBu)(dppha) 5 ]. Whereas inorganic-organic zinc clusters have been exploited as secondary building units of noncovalent porousm aterials, [17] our studies revealed that discrete [RZn(O 2 PR' 2 )]-type clusters act as shape-selective molecular buildingu nits and exhibit au nique capability for self-assembly, producing extended 3D networks with open channels. Moreover,a lkylzinc phosphinates appear to be efficient and easy-toprepareo rganozinc precursors of ZnO NCs capped with strongly anchored phosphinate ligand shells, which provides a new tool for the design, preparation,a nd functionalization of novel ZnO-based nanomaterials.…”
Section: Resultsmentioning
confidence: 81%
“…The self-assembly of molecularb uilding blocks through noncovalenti nteraction-driven self-assembly processes or the formation of open-frameworks tructures represents av ery attractive wayt oc reate al arge varietyo fo rdered functional structures. [17,18] Interestingly,a lkylzinc phosphinates with aq uasicube-shaped core exhibit au nique capacity for shape-driven self-assembly to produce extended 3D networks. Ad etailed analysiso ft he crystal structures of 1 4 and 3 4 revealed that the first stage of the self-assembly processi nvolves shape-locking of [RZn(O 2 PR' 2 )]-type clusters, which results in the formation of extended2 Dl ayered networks with voids directed along the caxis and filled by toluene molecules (Figure 1a (Figure 1d and Figure S10) (for 3 4 ).…”
Section: Synthesis and Structural Study Of Alkylzinc Phosphinatesmentioning
confidence: 99%
“…The tautomeric equilibrium between lactam (2-pyridone) and lactim (2-hydroxypyridine) forms enables different coordination of this ligand via a nitrogen and/or oxygen donor atom [14][15][16]. The observed metal complexes with 2-pyridone [14,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] show predominantly the lactam form in the solid state and in solution [16,34], but examples with the lactim form are also known for Pt, Ir, and Ru [35][36][37][38][39][40]. Different coordination modes of 2-pyridone and 3-hydroxypyridine can also have a distinctive influence on molecular arrangements in the solid state as a result of different non-covalent intermolecular interactions, because the 2-pyridone ligand can act as a hydrogen bond donor and acceptor, whereas 3-hydroxypyridine can act only as a hydrogen bond donor (Scheme 1).…”
Section: Introductionmentioning
confidence: 98%
“…These porous metallophosphate materials, displaying variable dimensionalities and structures, have proven to be unexcelled for a long time due to their applications in catalysis and other areas . Starting from a dibasic phosphoric acid monoester (instead of the H 3 PO 4 ) and a divalent main group or transition‐metal ion (instead of trivalent aluminum), our research group has extensively investigated the synthesis of a variety of organic soluble metal phosphate clusters and their applications in MOF chemistry, catalysis, molecular recognition, and molecular magnetism …”
Section: Introductionmentioning
confidence: 99%
“…The fact that four zinc centers occupying the alternate corners of the cubane in 1 are highly Lewis acidic has led to the successful joining of these cubanes by structurally diverse substituted pyridines or ditopic spacer ligands, such as 4,4′‐bipyridine (Scheme ) . An alternative strategy to build porous solids starting from D4R zinc phosphate cubanes would be by diligently combining the principles of both MOF and COF chemistries.…”
Section: Introductionmentioning
confidence: 99%